Spleen rupture during labor - Camila Karsburg Bessow; Ana Lúcia Letti Müller; Rosi Pereira Balbinotto; Jaqueline Neves Lubianca (Clinical and Biomedical Research, 2016)
Background: A ruptured splenic artery aneurysm is rare but potentially fatal and has a greater chance of occurring during pregnancy.